Preparation of Graphene Oxide and Its Application as Substrates for SERS - Xiaodong Li (Journal of Chemistry)
Graphene oxide (GO) was synthesized by a modified Hummer’s method and was then reduced by the hydrothermal process. Both GO and reduced GO (rGO) were employed as surface-enhanced Raman scattering (SERS) substrates to detect rhodamine 6G (R6G). After adsorbed on the surface of GO, the fluorescence background of R6G was highly quenched, and its Raman scatterings were enhanced. When adsorbed on the surface of rGO, the fluorescence background was further quenched at the price of lower SERS intensity. The results displayed that oxygen groups on the surface of GO had positive effect on the SERS effect of GO. The amount of oxygen groups on the surface of GO should be one key parameter to adjust the SERS activity of GO.